2021
DOI: 10.1111/ppe.12754
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood weight gain: Latent patterns and body composition outcomes

Abstract: Background Despite early childhood weight gain being a key indicator of obesity risk, we do not have a good understanding of the different patterns that exist. Objectives To identify and characterise distinct groups of children displaying similar early‐life weight trajectories. Methods A growth mixture model captured heterogeneity in weight trajectories between 0 and 60 months in 1390 children in the Avon Longitudinal Study of Parents and Children. Differences between the classes in characteristics and body si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…For example, a one-unit higher maternal BMI might be related to a 0.05 kg/m 2 /year steeper offspring BMI trajectory on average, but growth mixture modelling might provide additional information that higher maternal BMI is associated with greater odds of their child belonging to a small adolescent-onset of underweight group. A recent paper by Dos Santos et al found that maternal obesity was related to membership of unhealthy latent BMI trajectory classes (e.g., always obese) in the 2001 cohort [ 22 ], and similar findings have been reported in other studies [ 7 , 8 , 10 , 23 , 24 ]. The majority of this literature, however, does not consider paternal BMI and inadvertently contributes to the “imbalance of DOHaD [development origins of health and disease] research towards the study of maternal pregnancy exposures” [ 25 , 26 ].…”
Section: Introductionsupporting
confidence: 69%
“…For example, a one-unit higher maternal BMI might be related to a 0.05 kg/m 2 /year steeper offspring BMI trajectory on average, but growth mixture modelling might provide additional information that higher maternal BMI is associated with greater odds of their child belonging to a small adolescent-onset of underweight group. A recent paper by Dos Santos et al found that maternal obesity was related to membership of unhealthy latent BMI trajectory classes (e.g., always obese) in the 2001 cohort [ 22 ], and similar findings have been reported in other studies [ 7 , 8 , 10 , 23 , 24 ]. The majority of this literature, however, does not consider paternal BMI and inadvertently contributes to the “imbalance of DOHaD [development origins of health and disease] research towards the study of maternal pregnancy exposures” [ 25 , 26 ].…”
Section: Introductionsupporting
confidence: 69%
“…Clues with respect to the mechanism of programming by maternal obesity may be gained from studies of GDM because the long‐term health of offspring exposed to GDM is largely the same as that observed with maternal obesity, although obesity can occur without GDM and vice versa. As early as 2 years of age, GDM offspring exhibit markedly greater risk of obesity 113 and this persists into childhood 114–116 . Dabelea et al 117 .…”
Section: Mechanistic Perspectives On Programming By Obesitymentioning
confidence: 99%
“…As early as 2 years of age, GDM offspring exhibit markedly greater risk of obesity 113 and this persists into childhood. [114][115][116] Dabelea et al 117 followed up sibling pairs where one of the pair had been exposed to GDM and the other had not. Among people in their early 20s, those who had experienced GDM in foetal life had a BMI on average 2.6 kg m -2 greater than unexposed siblings.…”
Section: Mechanistic Perspectives On Programming By Obesitymentioning
confidence: 99%
“…A common example of phenotypes defined in terms of trajectories of ASR-related constructs with a single variable is trajectories for weight gain or BMI. Norris et al ( 72 ), for instance, examined weight trajectories from 0 to 60 months of age using GMM to identify five groups of individuals with different average trajectories. The subgroups included “average,” “high-decreasing,” and “stable-high” BMI trajectories.…”
Section: Person-centered Approaches and Their Application In Asr Phenotype Researchmentioning
confidence: 99%